Feasibility of hearing preservation for residual hearing with longer cochlear implant electrodes. (2nd December 2018) - Moteki, Hideaki; Nishio, Shin-Ya; Miyagawa, Maiko; Tsukada, Keita; Noguchi, Yoshihiro; Usami, Shin-Ichi
Abstract: Background: Hearing preservation is thought to be achievable following atraumatic surgery with thin cochlear implant electrodes; therefore, the surgical approach and implant electrode design are crucial considerations. Objective: To assess the feasibility of hearing preservation with long electrodes for patients meeting the criteria for conventional cochlear implantation. Methods: One hundred and two patients (132 ears) who underwent cochlear implant surgery were analyzed. Inclusion criteria included measurable residual hearing in the low frequency before implantation and not meeting the criteria for electric acoustic stimulation (EAS). Results: Of the 18 patients with residual hearing in the low frequency enrolled, 17 subjects (94.4%) retained low frequency hearing. A younger age at surgery tended to contribute to better hearing preservation than that observed in older patients. There was no clear trend regarding the influence of insertion depth angle of the electrode on hearing preservation. Conclusion: It is possible to achieve hearing preservation in the lower frequency by the use of longer electrodes. This study underscores the importance of atraumatic surgery, even for patients with only limited residual hearing, and longer electrodes should be adopted for EAS.